ASTROPHYSICAL S-FACTOR AND REACTION RATE OF THE RADIATIVE 3H(p,)4He CAPTURE - A.V. Dzhazairov-Kakhramanov; L.T. Karipbayeva (Academic Scientific Journal of Computer Science, 2019)
Calculations of the astrophysical S-factor of the proton radiative capture on 3H at energies from 1 keV to 10 MeV in the frame of Modified Potential Cluster Model with classification of orbital states of nuclear particles according to Young tableaux and isospin were carried out and the possibility of description of available experimental data in the energy range from 50 keV to 5 MeV is shown. We calculated rate of this reaction from 0.05 to 2 T9, because it can play certain role in the primordial nucleosynthesis of the Universe.